2007
DOI: 10.1007/s10327-007-0015-y
|View full text |Cite
|
Sign up to set email alerts
|

Root and stem rot of chrysanthemum caused by five Pythium species in Japan

Abstract: Root and stem rot with wilt of above ground parts of cultivated chrysanthemums was first found in Ibaraki, Toyama and Kagawa prefectures, Japan in 2002 and2003. Pythium species were isolated from the diseased tissues and identified as P. dissotocum, P. oedochilum, P. sylvaticum, P. ultimum var. ultimum and asexual strains of P. helicoides based on their morphologies and sequences of rDNA-ITS region. All the Pythium species were strongly pathogenic to chrysanthemums in pot conditions and were reisolated from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…Fig. 4 Growth rate of P. helicoides isolates GDGJ3 and GDGJ6 on PDA P. helicoides, which is more frequent in tropical and subtropical regions, is a well-known plant pathogen that has been reported to cause leaf, stem, root and crown rot, damping off, and leaf blight in several host plants worldwide (Chellemi et al 2000;Drechsler 1930;Guha Roy and Hong 2008;Kageyama et al 2002;Tsukiboshi et al 2007;Van der Plaats-Niterink 1981;Watanabe et al 2007;Yang et al 2013 (Dou et al 2010;Huang 2009), but there are no records of its occurrence in citrus. Therefore, this is the first report of P. helicoides causing stem rot of Shatangju mandarin seedlings in China.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Fig. 4 Growth rate of P. helicoides isolates GDGJ3 and GDGJ6 on PDA P. helicoides, which is more frequent in tropical and subtropical regions, is a well-known plant pathogen that has been reported to cause leaf, stem, root and crown rot, damping off, and leaf blight in several host plants worldwide (Chellemi et al 2000;Drechsler 1930;Guha Roy and Hong 2008;Kageyama et al 2002;Tsukiboshi et al 2007;Van der Plaats-Niterink 1981;Watanabe et al 2007;Yang et al 2013 (Dou et al 2010;Huang 2009), but there are no records of its occurrence in citrus. Therefore, this is the first report of P. helicoides causing stem rot of Shatangju mandarin seedlings in China.…”
Section: Discussionmentioning
confidence: 98%
“…In the USA, it was found that P. helicoides was virulent in several crops such as bell pepper and caused root and stem rot of Begonia (Chellemi et al 2000;Yang et al 2013). In Japan, the species was identified to infect miniature r o s e , a n d t o c a u s e r o o t a n d s t e m r o t o f Chrysanthemum and Kalanchoe (Kageyama et al 2002;Tsukiboshi et al 2007;Watanabe et al 2007). The disease transmission test on miniature roses showed that the disease spread throughout the bench 10 days post-inoculation of the plants placed in the bench center (Kageyama et al 2002).…”
Section: Introductionmentioning
confidence: 98%
“…), which originated in Asia and Northeastern Europe, has been cultivated for more than 1600 years [1,2]. It is widely cultivated for ornamental, culinary, and medicinal uses throughout the world.…”
Section: Introductionmentioning
confidence: 99%
“…The total amount of the macro-elements applied with the mineral and organic fertilizers was as follows: NPK: 60.0 mg N pot −1 ; 13.1 mg P pot −1 ; 41.2 mg K pot −1 ; L1: 36.8 mg N pot −1 ; 0.5 mg P pot −1 ; 9.1 mg K pot −1 ; L2: 35.0 mg N pot −1 ; 2.9 mg P pot −1 ; 40.4 mg K pot −1 ; L3: 18.4 mg N pot −1 ; 0.3 mg P pot −1 ; 24.6 mg K pot −1 ; L4: 15.1 mg N pot −1 ; 3.3 mg P pot −1 ; 12.5 mg K pot −1 ; and L5: 27.4 mg N pot −1 ; 4.1 mg P pot −1 ; 14.6 mg K pot −1 . Notes: 1 The concentration of N, P, and K in the mineral and organic fertilizers was determined by the chemical analysis methods in Section 2.3; 2 OFDC, Organic Food Development Center; 3 EU, European Union.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogen also affects cutting roses grown in rock wool culture, a hydroponic culture system in which the nutrient solution is recirculated. Recently, P. helicoides was reported to cause root and crown rots of strawberry and damping-off of chrysanthemum (Suzuki et al 2005;Watanabe et al 2005;Tsukiboshi et al 2007). Furthermore, P. aphanidermatum and P. myriotylum are also important pathogens in hydroponic culture systems, causing root rot of cucumber, tomato, tobacco, bell pepper, floral crops, lettuce, artichoke and other many crops (Moulin et al 1994;Jenkins and Averre 1983;Anderson et al 1997;Chellemi et al 2000;Moorman et al 2002;Stanghellini et al 1998Stanghellini et al , 2000a.…”
Section: Introductionmentioning
confidence: 97%